Real-World Virtual Reality With Head-Motion Parallax - Thatte, Jayant (IEEE computer graphics and applications, 2021)
Most of the real-world virtual reality (VR) content available today is captured and rendered from a fixed vantage point. The visual-vestibular conflict arising from the lack of head-motion parallax degrades the feeling of presence in the virtual environment and has been shown to induce nausea and visual discomfort. We present an end-to-end framework for VR with head-motion parallax for real-world scenes. To capture both horizontally and vertically separated perspectives, we use a camera rig with two vertically stacked rings of outward-facing cameras. The data from the rig are processed offline and stored into a compact intermediate representation, which is used to render novel views for a head-mounted display, in accordance with the viewer's head movements. We compare two promising intermediate representations-Stacked OmniStereo and Layered Depth Panoramas-and evaluate them in terms of objective image quality metrics and the occurrence of disocclusion holes in synthesized novel views